2019
DOI: 10.3390/s19092198
|View full text |Cite
|
Sign up to set email alerts
|

Delamination Detection in Polymeric Ablative Materials Using Pulse-Compression Thermography and Air-Coupled Ultrasound

Abstract: Ablative materials are used extensively in the aerospace industry for protection against high thermal stresses and temperatures, an example being glass/silicone composites. The extreme conditions faced and the cost-risk related to the production/operating stage of such high-tech materials indicate the importance of detecting any anomaly or defect arising from the manufacturing process. In this paper, two different non-destructive testing techniques, namely active thermography and ultrasonic testing, have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…In this framework, the use of coded modulated heating stimuli in combination with the pulse-compression technique, also known as PuCT or thermal wave radar imaging [34], has proved to be a beneficial and robust NDT method in which a given heat amount is delivered to the SUT by spreading it over an arbitrarily long time period so as to limit the heat peak power below a certain value [35]. Thanks to the pulse-compression technique, almost the same information of an equivalent pulsed thermography test of the same delivered energy is retrieved and, at the same time, a high flexibility in the heating process is obtained.…”
Section: Pulse-compression Thermographymentioning
confidence: 99%
See 1 more Smart Citation
“…In this framework, the use of coded modulated heating stimuli in combination with the pulse-compression technique, also known as PuCT or thermal wave radar imaging [34], has proved to be a beneficial and robust NDT method in which a given heat amount is delivered to the SUT by spreading it over an arbitrarily long time period so as to limit the heat peak power below a certain value [35]. Thanks to the pulse-compression technique, almost the same information of an equivalent pulsed thermography test of the same delivered energy is retrieved and, at the same time, a high flexibility in the heating process is obtained.…”
Section: Pulse-compression Thermographymentioning
confidence: 99%
“…ICA was used in the active thermography configuration for analyzing panel paintings [52] and impacted composite materials made by natural fibres [53], both subjected to a preliminary long-pulse radiation. The use of PCA and ICA in combination with PuCT, with both coded or frequency-modulated excitation, was addressed instead by Mulavesaala and co-workers in [54,55], and by some of the present authors in [35].…”
Section: Integration Among Puct Hsi and Post-processing Analysesmentioning
confidence: 99%
“…Such an approach was previously applied for composite inspections using the through transmission technique [ 9 , 10 , 11 ]. Studies [ 12 , 13 , 14 , 15 ] showed that air-coupled testing shows promising results in the detection of internal defects in composites, and techniques such as air-coupled imaging using the pulse compression method [ 16 , 17 ] can be used for improving the signal-to-noise ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a large number of non-destructive methods have been reported by the scientific and industrial community for the analysis of delamination defects in fiber-reinforced polymer (FRP) materials. Most of the reported papers suggested the techniques of ultrasounds [ 9 , 10 ], thermography [ 11 ], shearography [ 12 ], radiography [ 13 ], acoustic emission [ 14 ], and vibration-based solutions [ 15 , 16 , 17 , 18 ] for the detection and characterization of different defects in composite materials. Among the aforementioned techniques, vibration-based methods are considered as one of the most popular methods for damage detection because of their simplicity, versatility, and low cost, which facilitates their application to a more industrial environment.…”
Section: Introductionmentioning
confidence: 99%